Production of organic Saffron (Crocus sativus) using biofertilizer and vermicompost - LATIF, SABIA; ZARGAR, M Y; NEHVI, F A; AJAZ, MISBAH; AHMAD, MALIK SAJAD (The Indian Journal of Agricultural Sciences, 2022)
An experiment was conducted at SKUAST-Kashmir during 2018–19 and field trials were conducted at Dryland Agriculture research Station of SKUAST-K and Saffron Research Station, Pampore, Jammu and Kashmir. Results of the present investigation revealed that application of vermicompost, biofertilizer alone or in combination were beneficial in increasing commercial production of saffron. It encouraged more blossoms, which directly influenced the yield of saffron in both locations. At the Dryland Agriculture Research Station, SKUAST-Kashmir application of Azotobacter @11.5 g + 115 g sand + recommended dose of vermicompost of FYM recorded highest number of flowers/plot (139), fresh flower weight (40.10g), and pistil weight (1.17g), followed by treatment level T6 (Azotobacter @11.5 g + 115 g sand + recommended dose of vermicompost of kitchen waste), similar T10 (Azospirillum @11.5 g + 115 g sand + suggested amount of FYM vermicompost). Similar trends in the results were seen at the Pampore Saffron Research Station. Significant changes between treatments for all the features were found in the analysis of variance for the floral and corm properties. For all features, with the exception of the number of flowers, flower weight, and corm weight, location impacts were also significant.